DAMPAK EKONOMI FLU BURUNG TERHADAP KINERJA INDUSTRI PERUNGGASAN DI PROVINSI JAWA TENGAH - SAPTANA -; EDI BASUNO; YUSMICHAD YUSDJA (SOCA: Jurnal Sosial Ekonomi Pertanian, 2005)
Avian Influenza (AI) is poultry infectious disease and can cause dead. Apart from that, as awhole, AI has significant socio-economic impacts on poultry industry. In general, this particular studyaims to observe economic impact of AI towards performance of poultry industry in Central JavaProvince. Economic impact caused by AI towards poultry industry varies from region and from the typeof poultry. The most suffer was experienced by quail and layers farms, while impact on broilersrelatively small. Integrated type of farms suffered more compared to independent farms that spread outwith a better natural barrier. On breeding farms, AI had reduced DOC production to 40 percent and alsoreduced DOC selling price far below break even point (BEP). On feed industries, 14, 58 percentreduction on production was occurred, however, it does not have impact on feed selling. Meanwhile,economic impact of AI towards chicken slaughtering house, broiler middlemen and retailers reduced by40, 80 and 33 – 50 percent respectively and it has impact on temporary selling price. Economic impactof AI towards egg middlemen and egg retailers also decreased by 66, 67 and 53 percent respectively,however it did not influence egg selling price. Relevant policy implications are: (1) implements earlydetection; (2) applies quick and accurate data monitoring; (3) implement tight bio-security; (4) recoverypolicies at the farm level, with compensation and low interest rate credit supports.